Mathematical modelling and solution of pipeline laying problem. (1st January 2012) - Wang, Na; Xu, Qingzheng; Zhang, Yufeng
Developing a general approach to the pipeline laying problem with constraints has both theoretical and practical value. Considering the unit expense of oil pipeline, economic difference for different areas, and qualification and charge of different manufacturers, the mathematical model with the lowest total cost is established. Based on the basic principle for calculating the extremum of multivariate function and the method of undetermined coefficients, a general mathematical method is proposed and the analytical solution to the pipeline laying problem is given in this paper. The results of theoretical calculation and simulation experiments show clearly that, the general approach proposed in this paper is effective, especially for engineering design purposes.